The position of the Nusantara Capital City from a national security perspective - Herdiawanto, Heri (Faculty of Social and Political Science, Universitas Airlangga, 2023)
The relocation of the capital city to East Kalimantan is a megaproject contained in the National Medium-Term Development Plan (RPJMN) for 2020-2024. Despite the pros and cons, this megaproject is targeted to be completed in the next 15 years. This research focuses on explaining the impact of the relocation of the Nusantara Capital City from a national security perspective for Indonesia in the future, considering that Indonesia is a large country in Southeast Asia and the backbone of ASEAN. To answer the question, this research uses an explorative qualitative approach, with library research as an analysis technique. This technique collects the information by collecting and analyzing the documents, journals, books, and media information related to the object of research. The theory used in this research is national security and it is found that the policy of relocating the capital city will have a positive impact on Indonesia in the future, as seen from various national security sectors such as from the economy to the environment. On the other hand, it can also pose a new threat to Indonesia from the socio-cultural sector.